Рання прегравідарна підготовка жінок із невиношуванням вагітності на тлі гіперандрогенії - Семенюк, Л. М.; Яроцький, М. Є.; Дашук, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2013)
A study of vaginal and intestinal biocenosis in patients with recurrent miscarriages and hyperandrogenism was made. In terms of early pregravidal training program conducted 4R, aimed at restoring the gastrointestinal and vaginal balance. As a result of marked improvement in the general condition, the symptoms of intestinal dyspepsia, reduction or complete elimination of vaginal discharge, redness or swelling of the vagina, burning and itching disappeared. In 34.6 % of cases normalization of menstrual function and androgen levels were shown.